Strategi Pemasaran dan Pengelolaan Keuangan bagi Usaha Mikro, Kecil dan Menengah di Masa Pandemi Covid-19 - Ayu Ekasari; Victor Siagian; Anita Roosmalina Matusin; Yuana Jatu Nilawati (Penerbit Goodwood, 2021)
Purpose: This activity aims to provide counselling for micro, small, and medium enterprises affected by the Covid-19 pandemic because they cannot open their stores at Blu Plaza in Bekasi, West Java. The Covid-19 pandemic has affected this community greatly since 2020, and the members of UMKM Blu Plaza asked for advice regarding marketing and financial aspects to survive. Research Methodology: There were seventeen participants counselling was conducted online using Zoom application by giving training materials and asked the participants to be proactive by asking questions and doing some real exercises. Results: The counselling results show that participants are able to do some exercises about working capital and the cost of goods sold. Also, their understanding of selling products via online marketing has improved. The post counselling questionnaire shows that the participants are very interested in the topics and asked for more time to participate in the following community service activity. However, the participant-trainer interaction was not optimal due to the pandemic situation. Future activities can use additional features with the help of information technology to attract more participants. Conclusions: By implementing online community service, counsellors can interact with the participants and ask them to do some exercises. This is a way to increase people’s participation, and results showed that their understanding of the topics increased.